2012
DOI: 10.5455/2319-2003.ijbcp003812
|View full text |Cite
|
Sign up to set email alerts
|

Prescription auditing and drug utilization pattern in a tertiary care teaching hospital of western UP

Abstract: Background: In India, a proper reporting of medication errors in the hospital is not available. Drugs worth crores of rupee are consumed every year but a substantial part of these drugs are irrationally prescribed. In order to promote rational drug usage standard policies on use of drugs must be set, and this can be done only after the current prescription practices have been audited. The prescriptions were analyzed based on the objectives of the study in order to promote rational use of drugs in a population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 9 publications
8
60
1
Order By: Relevance
“…In our study percentage prescription of antibiotic was according to ideal value. Similar value was also present in study done by Afroj Abidi et al, 2012higher in studies done by Binu et al, 2013 (41.98%), 16 U.A. Chandelkar et al, 2014 (31.8%), 17 Harmeet et al, 1998 (42.8%).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In our study percentage prescription of antibiotic was according to ideal value. Similar value was also present in study done by Afroj Abidi et al, 2012higher in studies done by Binu et al, 2013 (41.98%), 16 U.A. Chandelkar et al, 2014 (31.8%), 17 Harmeet et al, 1998 (42.8%).…”
Section: Discussionsupporting
confidence: 78%
“…12 This is much higher than the recommended limit of 2.0. This value is also higher in studies done by Afroz et al, 2012 (4.22), 13 P. Geetha et al, 2015 (4.38).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Various studies have revealed that prescribing medicines by brand name has become a routine practice. 13,14 Prescribing by generic name should be encouraged at an early stage of medical practice to promote RUM. It is encouraging to know that almost all the respondents were always aware of the ingredients of the drug prescribed and they inform the patient regarding disease, drug therapy, and regular follow-up and monitoring of drug therapy.…”
Section: Figure 1: Sources Of Drug Information Preferred By Intern Anmentioning
confidence: 99%